Situación emocional y enfermedades de transmisión sexual de las trabajadoras sexuales que acuden al Centro de Salud N° 1 de Loja. - Cajamarca Llivigañay, Rita Dayci (2013)
This research was conducted with sex workers who come to the health center Shop No. 1 of Loja, with the aim of determining how emotions influence compared to contracting sexually transmitted diseases. The results hint at the women investigated in disease prevention , medical checks are always performed , they have been infected with sexually transmitted diseases : Triconomiasis , Human Papillomavirus , Gonorrhea , Genital Herpes and Syphilis , in the presence of these diseases reflect emotions as , fear , anger, anxiety , sadness , disgust and indifference , which involve uncertainty about the ability to withstand or handle this situation , affecting daily coexistence of sex workers , in full, at work and trying to privacy carry some measure of their consequences. Emotional care of sex workers is adequate, but the clarity of emotions and emotional repair are scarce, results should be corrected, as there is a decline reflecting negative emotions that alter their mental state. The sample of this study, we investigated 353 sex workers, the analysis results were used supporting tools such as survey, observation guide and interview managers of brothels. To tabulate data collected were prepared and cross simple tables, using Microsoft Word and results in tables are analyzed and interpreted based on the conceptual framework developed for research. The conclusions and recommendations are a synthesis that expresses the emotional situation of the workers who come to the health center Shop No. 1 of Loja, against sexually transmitted disease.